Rabindranath Tagore, Amartya Sen, and the early Indian classical period : the obligations of power - Leavitt, Neal, 1974- (Lanham, Maryland : Lexington Books, 2022)
"This book examines the ethical standard of the obligations of power articulated by philosophers Rabindrinath Tagore and Amartya Sen. The author argues that Tagore and Sen focused on the need to diminish all states' capacity for violence, regardless of regime type"--
Introduction -- Part I: Buddha and Ashoka: 1. Violent Conduct -- 2. A Legal Code -- 3. Persons and Animals -- 4. From the Ethical to the Political -- 5. New Norms -- Conclusion to Part I -- Part II: A Development Ethic: 6. Living Reality -- 7. The International System -- 8. Human Security -- 9. Open Impartiality -- Bibliography -- About the Author.
Includes bibliographical references and index.
Keywords: Tagore, Rabindranath, -- 1861-1941 -- Political and social views; Sen, Amartya, -- 1933- -- Political and social views; Power (Social sciences); Political violence -- Prevention